Microbiomes in Soils Exposed to Naturally High Concentrations of CO2 (Bossoleto Mofette Tuscany, Italy) - Fazi, Stefano; Ungaro, Fabrizio; Venturi, Stefania; Vimercati, Lara; Cruz Viggi, Carolina; Baronti, Silvia; Ugolini, Francesca; Calzolari, Costanza; Tassi, Franco; Vaselli, Orlando; Raschi, Antonio; Aulenta, Federico (Frontiers in Microbiology, 2019)
The direct and indirect effects of extremely high CO2 levels on biogeochemical processes in soil are poorly understood. At this regard, this study investigated a sinkhole in Italy where long-term emission of CO2 is associated with accumulation of carbon in the topsoil and removal of inorganic carbon in low pH environment at the bottom of the sinkhole. The comparison between interstitial soil gases with those collected in an adjacent bubbling pool and the analysis of the carbon isotopic composition of CO2 and CH4 clearly indicated the occurrence of CH4 oxidation and negligible methanogenesis in soils at the bottom of the sinkhole. Extremely high CO2 concentrations resulted in higher microbial abundance (up to 4×10-9 cell g-1 DW) and a lower microbial diversity by favoring bacteria already reported to be involved in acetogenesis in mofette soils (i.e. Chloroflexi and Acidobacteria). Laboratory incubations to test the acetogenic and methanogenic potential clearly showed that all the mofette soil microcosms supplied with hydrogen gas displayed a remarkable CO2 fixation potential, primarily due to the activity of acetogenic microorganisms. By contrast, negligible production of acetate occurred in control microcosms incubated with the same soils, under identical conditions, without addition of hydrogen gas. In this study we report how changes in diversity and functions of the soil microbial community - induced by high CO2 concentration - create peculiar biogeochemical profile. CO2 emission affects carbon cycling through: i. inhibition of the decomposition of the organic carbon and ii. promotion of CO2-fixation via the acetyl-CoA pathway. Sites naturally exposed to extremely high CO2 levels could potentially represent an untapped source of microorganisms with unique capabilities to catalytically convert CO2 into valuable organic chemicals and fuels.